Analisis Peluang Dan Tantangan Koperasi Desa Merah Putih Dalam Pemberdayaan Ekonomi Desa - Syafrizal, Rodi; Aulia, Cindi; Hasyim, Liza Widya (Accounting Progress, 2025)
Rural-urban inequality remains a structural problem in national economic development. This disparity is characterized by low rural income, limited infrastructure, and weak human resource capacity. The "Koperasi Desa Merah Putih" (Red and White Village Cooperative) is present as a potential solution to bridge this gap through local economic empowerment. This study aims to analyze the opportunities and challenges faced by the cooperative in empowering the village economy. This research employs a descriptive qualitative approach with literature study and phenomenological analysis methods. The results indicate that the cooperative has significant opportunities in managing local natural resources and utilizing village funds for productive businesses. However, major challenges include low managerial capacity, limited capital access, and strict market competition with established private sectors. The study concludes that revitalization of the cooperative through human resource training, digitalization, and strategic partnerships is essential to strengthen the rural economic structure.